Presentation of the research programme «MISSIVA - Lettres de femmes dans l’Europe medievale (Espagne, France, Italie, Portugal, VIIIe-XVe siecle)» (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This text is an introduction to «MISSIVA: women’s letters in Medieval Europe (Spain, France, Italy, Portugal, VIIIth-XVth centuries)», which is a program from the EHEHI–Casa de Velázquez (Madrid) running over the 2018-2021 time period. MISSIVA is supported by an extensive network of researchers from France, Spain, Italy and Portugal specialized in various fields (philology, cultural history, political history, women’s history, etc.).This wide and innovative program is meant to enlighten the role women might have played in shaping the political destiny of kingdoms. In particular, this reflection is centered on the function of women’s letters, on their informative and performative nature, on their political and literary dimensions, as well as the models and tones their make use of. The way links of mediations between women are created through these scriptures is also explored. Finally, these documents are examined for markers that could be considered as typically feminine. This article presents a summation of the work performed since the inception of the project and revisits the first advances from the reflection that took place during the scientific meetings that were held.
Keywords: MISSIVA; Letters; Women's letters; Power; Medieval Europe; 8th-15th centuries